Ukuziphendulela kubahlaziyi besiZulu - Ntombela, Berrington (Journal for Language Teaching, 2024)
ENGLISH TITLE: Responding to isiZulu reviewers Writing in African languages remains a challenge especially when your writing is going to be judged through the lenses of a colonial language. this is because the dominant languages in education, such as English preside over academic literacy and therefore dictates how academic writing should be carried out. This paper is based on the reviewers’ comments about a chapter that was submitted for possible publication in a book. The chapter was written in isiZulu and the reviewers provided their review in isiZulu as well. This paper therefore interrogates these comments using autoethnography which allows the ‘self’ of the researcher to be part of the investigated. The researcher responds to these comments in order to establish their basis. The analysis indicates that whilst the reviewers provided useful comments for the improvement of the chapter, some of their comments revealed their ignorance about the research paradigm chosen by the researcher. The conclusion is that comments based on reviewers’ ignorance of the researcher’s chosen method of investigation are likely to discourage writers who might not have the energy to explain themselves to the reviewers. Iqoqa Ukubhala ngezilimi zase-Afrikha kuhlala kuyinselelo ikakhulukazi uma ukubhala kwakho kuzokwahlulelwa ngokusebenzisa indlelakubuka yolimi lwamakholoni. Lokhu kungenxa yokuthi izilimi ezihamba phambili emfundweni, njengesiNgisi zengamela ukufunda nokubhala kwe-zemfundo, ngakho-ke yizo ezibeka imithetho yokubhala kwezemfundo nokuthi kufanele kwenziwe kanjani. Leli phepha lisekelwe emibonweni yabahlaziyi ma-yelana nesahluko esithunyelwe ukuze sishicilelwe encwadini. Isahluko sibhalwe ngesiZulu kanti abahlaziyi babuye banikeza imibono yabo nangesiZulu. Ngakho-ke leli phepha liphenya le mibono lisebenzisa i-autoethnography evumela ukuthi 'uqobo' lo mcwaningi abe yingxenye yophenyo. Umcwaningi uphendula le mibono ukuze athole isisekelo sawo. Uhlaziyo lu-khombisa ukuthi nakuba abahlaziyi beveze imibono ewusizo ukuze kuthuthukiswe isahluko, okunye uku-phawula kwabo kuveze ukungazi kwabo ngephuzu locwaningo elikhethwe um cwaningi. Isiphetho sidingida ukuphawula oku-sekelwe ekungazini kwabahlaziyi nge-ndlela yophenyo ekhethiwe yomcwaningi kungenzeka kudikibalise ababhali abangase bangabi nawo amandla okuzichaza kubahlaziyi